Wind pressure characteristics of elliptical retractable dome roofs. Issue 4 (4th July 2022) - Lee, Jong Ho; Kim, Yong Chul; Cheon, Dong Jin; Yoon, Sung Won
ABSTRACT: This study investigated the wind pressure characteristics of an elliptical plan retractable dome roof. Wind tunnel experiments were performed on elliptical dome roofs with varying wall height-to-span ratios (0.1–0.5) and opening ratios (0, 10, 30, and 50 %), where the opening ratio was defined as the ratio of the open area of the roof to the total area of the roof. The resulting peak pressure coefficients of the closed dome roof were then compared with those of the Japanese wind load code (AIJ-RLB (2015 )) as there are no current peak pressure coefficients for the cladding design code of elliptical dome roofs. The resulting peak pressure coefficients for each elliptical retractable dome roof opening ratio were also compared with those for the cladding design of spherical retractable domes proposed in previous research. Finally, based on the results of the comparative analysis, negative and positive peak pressure coefficients were proposed for the cladding design of elliptical retractable dome roofs.